Comparative evaluation of resin infiltration and remineralisation of noncavitated smooth surface caries lesions: 6-month results - Gözetici, Burcu; Öztürk Bozkurt, Funda; Toz Akalın, Tuğba (Quintessence Publishing Co Inc, 2019)
Purpose: To compare the therapeutic effects of the resin infiltration technique, self-assembling peptide (P11-4), and fluoride varnish application on white spot lesions (WSLs) on buccal surfaces based on LF pen measurements and LAA-ICDAS scores. Materials and Methods: The lesions of 113 patients from a total of 319 patients with at least four visible WSL on buccal surfaces were assessed by LAA-ICDAS and laser fluoresence (LF pen). To be included in the study, participants were required to have at least 4 buccal WLSs, each in different quadrants, with an LF pen score >= 8. Twenty-one patients were included in the study based on the laser fluoresence values. The lesions were randomly assigned into 4 groups (n = 21): IG (Icon), CRG (Curodont Repair), DG (Duraphat), and CG (control) groups. The treatment protocols were applied, but the control group received no treatment except regular brushing. Lesions were scored by LAA-ICDAS after 3 and 6 months and LF pen after 1 week, 3 and 6 months. Results: There was a statistically significant decrease in LF pen measurements of the control and the intervention groups after 6 months when compared to baseline. The greatest lesion regression was observed with IG (-23.25 +/- 18.21), which differed statistically significantly from CRG (-8.15 +/- 13.89), DG (-10.1 +/- 10.31) and CG (-4.15 +/- 9.72), followed by DG which differed statistically significantly from CG. Statistically significant differences were observed in the activity status of the lesions between baseline and 6 months, except for the control group. Conclusion: In this study, the lesion regression rates shown by mean LF pen values in all groups after six months encourages the management of non-cavitated smooth surface caries lesions with non-operative treatment approaches. Regular brushing and professional tooth cleaning seem to be effective for the management of WSLs on buccal surfaces, and resin infiltration or fluoride varnish might enhance the improvement of these lesions in moderate-to high-caries-risk individuals.
WOS: 000468765900002
PubMed ID: 30874252
Keywords: Fluoride Varnish; Laser Fluorescence; Resin Infiltration; Self Assembling Peptide; White Spot Lesion